2005
DOI: 10.1007/s11178-005-0367-8
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Trimethylsilylpropynoyl Chloride

Abstract: Trimethylsilylpropynoic acid reacts with thionyl chloride to give a mixture of trimethylsilylpropynoyl chloride and 3-chloro-3-trimethylsilyl-2-propenoyl chloride whose ratio depends on the reaction conditions (temperature, reactant ratio). Dimethylformamide almost does not catalyze the reaction. Treatment of trimethylsilylpropynoic acid with oxalyl chloride in the presence of 0.04 equiv of DMF at room temperature ensures selective formation of trimethylsilylpropynoyl chloride (yield 80%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
20
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 11 publications
0
20
0
Order By: Relevance
“…IR spectrum, ν, cm -1 : 1730 (C=O), 2160 (C≡C). 1 29 mmol) of amine II, and 0.3 ml of 0.8% hydrochloric acid (5 mol %) in 1 ml of acetonitrile was kept for 7 days at 25°C with intermittent shaking. The solvent was removed under reduced pressure, and the solid residue was analyzed by 1 H NMR spectroscopy.…”
Section: -(2-pyridyl)-2-trimethylsilylethynyl-12-dihydropyridine-3mentioning
confidence: 99%
See 1 more Smart Citation
“…IR spectrum, ν, cm -1 : 1730 (C=O), 2160 (C≡C). 1 29 mmol) of amine II, and 0.3 ml of 0.8% hydrochloric acid (5 mol %) in 1 ml of acetonitrile was kept for 7 days at 25°C with intermittent shaking. The solvent was removed under reduced pressure, and the solid residue was analyzed by 1 H NMR spectroscopy.…”
Section: -(2-pyridyl)-2-trimethylsilylethynyl-12-dihydropyridine-3mentioning
confidence: 99%
“…We previously showed that the triple bond in heteroelement-containing propynals R 3 EC≡CHO (E = Si, Ge) in the absence of a catalyst is inactive toward N-nucleophiles [1]. Primary amines add to silicon-and germanium-containing propynals and their carbon analog, 3-tert-butylpropynal, chemoselectively at the aldehyde group to give the corresponding Schiff bases in almost quantitative yield [2].…”
mentioning
confidence: 99%
“…This approach was partially reviewed in [2]. The presence of a trimethylsilyl group at triple C≡C bond stabilizes the latter so that it becomes inactive toward nucleophiles [3], organometallic compounds, and transition metal catalysts in various synthetic transformations [4]; as a result, regioselective cycloaddition of azides at the triple bond of various trimethylsilylalkynes becomes possible [5], the stability of compounds increases, and their solubility in organic solvents is improved.…”
mentioning
confidence: 99%
“…A mixture of 0.47 mmol of amide Ib-Ig,3.4 mg (5 mol %) of KF-Al 2 O 3 , and 5 ml of methanol was stirred for 20 min at room temperature. The mixture was then treated with 1 ml of 5% hydrochloric acid and extracted with diethyl ether (in the synthesis of IIb-IId) or chloroform (IIe-IIg), and the extract was dried over MgSO 4 and evaporated under reduced pressure.…”
mentioning
confidence: 99%
“…The presence of a silicon or germanium atom at the triple bond stabilizes propynal molecule and adducts derived therefrom, whereas subsequent demetalation under mild conditions could produce analogs with terminal triple bond. We previously showed that silicon-and germanium-containing propynals and their carbon analog react with primary amines in the absence of a catalyst chemoselectively at the aldehyde group with formation of the corresponding Schiff bases [2]. However, the nature of primary amine and reaction conditions could affect to a considerable extend both chemoselectivity of the addition reaction and structure of the products.…”
mentioning
confidence: 99%